The Bobbsey Twins in Washington - Hope, Laura Lee (Salt Lake City, UT : Project Gutenberg, 2004)
"The Bobbsey Twins in Washington" by Laura Lee Hope is a children's novel likely written in the early 20th century. A continuation of the beloved Bobbsey Twins series, this installment focuses on the adventures of Nan and Bert, along with their younger siblings, Flossie and Freddie, as they embark on a family trip to Washington, D.C. The story emphasizes themes of fun, imagination, familial bonds, and the excitement of travel experienced through the eyes of children. The opening of the book introduces the Bobbsey twins indulging in a playful afternoon at home after returning from a vacation. As they reminisce about their previous adventures, including one spent rescuing a boy on Blueberry Island, they engage in lively and imaginative games in their barn. However, their fun takes an unexpected turn when a pile of hay they are playing around slips, burying the younger twins, Flossie and Freddie. Amidst the ensuing panic, the older twins and their caregiver, Dinah, work together to dig the younger siblings out, only to discover that Flossie and Freddie have cleverly escaped to create their own mischief. This lighthearted trouble sets the stage for their upcoming trip to Washington, hinting at the adventures that await them in the capital. (This is an automatically generated summary.)
Release date is 2004-05-01
Produced by Juliet Sutherland, Charles Franks and the Online Distributed Proofreading Team
Keywords: Twins -- Juvenile fiction; Bobbsey Twins (Fictitious characters) -- Juvenile fiction; Siblings -- Juvenile fiction; Washington (D.C.) -- Juvenile fiction